The Comparison Of Engine Performance For Diesel And CNG Fuel Using GT-Power Software - R. A., Bakar; Abdul Rahim, Ismail; Ismail, Ali (2007)
Study on simulation of 4-stroke single cylinder engine is being presented. The engine with known specification is being modelled using one dimensional CFD GT-Power software. The same engine is used for different fuel; diesel and CNG. The operational parameters of the engine such as brake power, brake torque and brake specific fuel consumption which are dependent to engine speed are discussed. The results of engine performance from diesel and CNG fuel are compared to get the percentage of reductions.